Genre et statistiques : est-ce que « l’analyse de grappes » peut nous aider à comprendre la place du genre dans la recherche de meilleures conditions de travail ? - Karen Messing; France Tissot; Mélanie Lefrançois (Perspectives Interdisciplinaires sur le Travail et la Santé)
Work-family balancing (WFB), usually associated with women, is affected by scheduling, flexibility of working arrangements, organizational support, and other workplace parameters. Following a request from the women’s committee of a union confederation, we analysed retail work done on unpredictable, variable, extended schedules. Among other procedures such as workplace observations and study of company registers, we performed cluster analysis on the schedule choices of 247 male and 303 female staff.We found that: 4 clusters characterized schedule preferences; men and women were not uniformly distributed across clusters; choices varied within a gender. Diversity of choices was sufficient to allow the employer in principle to match preferences to schedules, but the employer showed little interest in WFB or gender equality. We conclude that cluster analysis lends itself to ergonomic analysis and to strategic intervention. We discuss its advantages and disadvantages for promoting workplace equality.